MOST EFFICIENT NLP TECHNIQUES IN OPTIMUM STRUCTURAL FRAME DESIGN - KARIHALOO, B. L. (Engineering optimization, 1993)
This paper identifies the two most efficient non-linear programming techniques for the solution of optimization problems of plane structural frames under multiple load systems. The problem is one of minimizing the mass or the frame subject to constraints on normal and shear stresses, the maximum transverse deflection and buckling load. In all, five different NLP techniques are tried, and it is found that the sequential linear and sequential convex programming techniques are the most efficient for the solution of the class of NLP problems under consideration